Structure and Expression Kinetics of Piscirickettsia Salmonis Sdha During Infection of Atlantic Salmon Macrophage-Like Cells - Maisey-Munoz, K (Academic Press, 2026)
The Gram-negative facultative intracellular pathogen Piscirickettsia salmonis infects salmonid fish species and causes economic losses in the Chilean salmon farming industry. Until now, the virulence factors and the mechanisms involved in establishing the fish infection are scarcely understood. P. salmonis can infect and survive in salmonid macrophages, and reports have shown that the Icm/Dot type-IV secretion system is part of the virulence factors that are essential for bacterial infection and replication inside bacteria-induced vacuoles. Since the Icm/Dot substrate SdhA has been identified as a key protein factor in maintaining the integrity of the Legionella-induced vacuolar membrane, we seek to explore the possibility that this substrate can also play a role in P. salmonis infection in fish. In this study we first confirmed the presence of the orthologous gene encoding SdhA of P. salmonis, demonstrating an evolutionary relationship with the sdhA genes of Coxiella burnetii and Legionella pneumophila. The in-silico analysis of the protein revealed a conserved structure and short linear motifs that suggest several potential functions related to vacuolar stability, autophagy, apoptosis, and vesicular transport processes that probably enable the pathogen to manipulate the defense mechanisms of the host cell. Additionally, for the first time, we demonstrated the early expression of sdhA at both the transcript and protein levels in infected salmon cells, suggesting that SdhA could interfere with the host pathogen eradication mechanisms shortly after infection. These results set up the basis to further studies on the functional role of SdhA in the host-pathogen interaction mechanisms associated with P. salmonis infection of salmonid fish. © 2025 Elsevier Ltd